Preserving Heritage, Marketing Tourism: Strategic Insights for Historical Tourism in West Sumatra - Gustiawan, Willson; Anugrah, Sufi (LACULTOUR: Journal of Language and Cultural Tourism, 2025)
West Sumatra holds significant potential for the development of historical tourism, with regions such as Bukittinggi, Padang, Payakumbuh, Batusangkar, Sawahlunto, Padang Panjang, Pariaman, and Bonjol showcasing a rich historical legacy from prehistoric times through the colonial era and the independence movement. This study employs a qualitative research approach combined with a descriptive method to explore the potential and marketing strategies of historical tourism in the area. The qualitative approach allows for a deep understanding of the region’s social and material realities, while the descriptive method systematically illustrates current events, conditions, and opportunities within the historical tourism sector. The research highlights the importance of local stories and narratives in enriching the visitor experience and differentiating West Sumatra as a historical tourism destination. Furthermore, the study emphasizes the critical role of collaboration between government bodies, local communities, and tourism practitioners in achieving sustainable tourism development. Integrating both visible and intangible resources, especially human capital, is crucial for crafting a compelling and resilient tourism strategy. Overall, West Sumatra’s rich historical assets present a substantial opportunity for economic growth and cultural preservation through thoughtfully developed historical tourism initiatives.